Association of Trait Resilience With Peritraumatic and Posttraumatic Stress in Patients With Myocardial Infarction. Issue 3 (April 2016) - Meister, Rebecca Elisabeth; Princip, Mary; Schnyder, Ulrich; Barth, Jürgen; Znoj, Hansjörg; Schmid, Jean-Paul; Wittmann, Lutz; von Känel, Roland
ABSTRACT: Objective: Acute myocardial infarction (MI) is a life-threatening condition, leading to immediate fear and distress in many patients. Approximately 18% of patients develop posttraumatic stress disorder in the aftermath of MI. Trait resilience has shown to be a protective factor for the development of posttraumatic stress disorder. However, whether this buffering effect has already an impact on peritraumatic distress and applies to patients with MI is elusive. Methods: We investigated 98 consecutive patients with acute MI within 48 hours after having reached stable circulatory conditions and 3 months thereafter. Peritraumatic distress was assessed retrospectively with three single-item questions about pain, fear, and helplessness during MI. All patients completed the Posttraumatic Diagnostic Scale (PDS) and the Resilience Scale to self-rate posttraumatic stress and trait resilience. Results: Multivariate models adjusting for sociodemographic and medical factors showed that trait resilience was not associated with peritraumatic distress, but significantly so with posttraumatic stress. Patients with greater trait resilience showed lower PDS scores ( b = −0.06, p < .001). There was no significant relationship between peritraumatic distress scores and PDS scores; resilience did not emerge as a moderator of this relationship. Conclusions: The findings suggest that trait resilience does not buffer the perception of acute MI as stressful per se but may enhance better coping with the traumatic experience in the longer term, thus preventing the development of MI-associated posttraumatic stress. Trait resilience may play an important role in posttraumatic stress symptoms triggered by medical diseases such as acute MI. Abstract : Supplemental digital content is available in the text.